Deciphering the interplay between fruit-associated metabolites and bacterial communities across four distinct mango cultivars - Zhang, Chuanfang; Wan, Rong; Nong, Siwei; Huang, Wei; Al-Rejaie, Salim S.; Wang, Fengzhen; Yang, Zhengzhou; Zhu, Zhengjie; Mohany, Mohamed (Frontiers in Plant Science, 2026)
Mango (Mangifera indica L.) fruit characteristics and health are strongly determined by their biochemical profiles and fruit-associated microbiome composition. However, the cultivar-specific interplay between the mango fruit metabolome and microbiome remains elusive. Here, we tracked differential changes in fruit metabolites and bacterial community composition in four economically important mango cultivars in China: Qingmang (QM), Yumang (YM), Tainong (TN), and Aomang (AM). Using untargeted metabolomics with liquid chromatography-mass spectrometry and high-throughput amplicon sequencing of bacterial 16S rRNA, we identified distinct metabolic profiles and the enrichment of a specific subset of microbiota unique to each cultivar. Different metabolites associated with nitrogen and carbon metabolism, biosynthesis of amino acids, secondary metabolites, and flavonoids were differentially abundant in the four mango cultivars. These classes of metabolites have been previously linked to fruit development, color, antioxidant capacity, and stress resistance. Importantly, significant positive correlations were found between specific bacterial taxa, such as Alcanivorax, Alistipes, Curtobacterium, Rikenella, Thiopseudomonas, Rikenella, and Vogesella and the accumulation of the metabolites ornithine, L-arginine, tricetin, casoxin D, mhppa sulfate, sorbitan palmitate, meconic acid and rengyoside B. These results indicate the critical role of mango cultivars in shaping the fruit-specific microbiomes and metabolites. Our findings provide a foundational understanding of mango fruit holobionts and offer novel insights into metabolic and microbial networks for developing strategies to enhance fruit quality and postharvest management.